2018
DOI: 10.1002/jcla.22440
|View full text |Cite
|
Sign up to set email alerts
|

A facile PCRRFLP method for genotyping of ITPA rs1127354 and rs7270101 polymorphisms

Abstract: We developed and validated a rapid and inexpensive PCR-RFLP technique for the detection of ITPA rs1127354 and rs7270101 gene polymorphisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
0
5
1
Order By: Relevance
“…The results showed that all of the 100 samples tested with PCR-RFLP and sequencing had exactly the same results, with 100% concordance. This demonstrates the utility of RFLP-PCR in studying SNPs with as high efficiency and reliability as Sanger sequencing, but at a reduced cost (Alavian et al 2018).…”
Section: Description Of the Polymerase Chain Reaction-restriction Fragment Length Polymorphism Technique And Exemplary Applicationsmentioning
confidence: 83%
See 1 more Smart Citation
“…The results showed that all of the 100 samples tested with PCR-RFLP and sequencing had exactly the same results, with 100% concordance. This demonstrates the utility of RFLP-PCR in studying SNPs with as high efficiency and reliability as Sanger sequencing, but at a reduced cost (Alavian et al 2018).…”
Section: Description Of the Polymerase Chain Reaction-restriction Fragment Length Polymorphism Technique And Exemplary Applicationsmentioning
confidence: 83%
“…One of the many practical examples of the application of RFLP-PCR in SNP genotyping is that performed by Alavian et al (2018) for the detection of the rs1127354 and rs7270101 polymorphisms associated with the inosine triphosphate pyrophosphatase (ITPA) gene. rs1127354 and rs7270101 SNPs are associated with a functional impairment in ITPase, resulting in anaemia protection in patients with chronic hepatitis C virus (HCV) infection undergoing ribavirin (RBV)-dependent regimens.…”
Section: Description Of the Polymerase Chain Reaction-restriction Fragment Length Polymorphism Technique And Exemplary Applicationsmentioning
confidence: 99%
“…Only patients with the undetectable viral RNA at CVR and at follow-up 24 weeks after completion of treatment were considered to have achieved SVR (Sustained viral response). The rate of SVR achievement was recorded as Per protocol analysis (PPA) means those patients were included in the study who adhered to anti-viral therapy till the finishing point and their post-treatment SVR status was assessed [ 21 ]. A decline in hemoglobin levels in HCV patients after using DAA (sofosbuvir ribavirin) treatment was also noted [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
“…ITPA gene amplification was performed with conventional PCR using (Thermo Scientific by Thermo Fisher) PCR master with 5–10 ng/µl DNA. Forward primer F-5′‐AGATGGGCAGCAGAGTTATCG‐3′ and the reverse primer was R‐5′‐AGACAGAGAAATCCAACCATCTTTTAAGAA 3′ [ 21 ]. The thermal cycle conditions were as described in our previous study [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation